2011
DOI: 10.1016/j.ajhg.2010.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Mitochondrial Seryl-tRNA Synthetase Cause Hyperuricemia, Pulmonary Hypertension, Renal Failure in Infancy and Alkalosis, HUPRA Syndrome

Abstract: An uncharacterized multisystemic mitochondrial cytopathy was diagnosed in two infants from consanguineous Palestinian kindred living in a single village. The most significant clinical findings were tubulopathy (hyperuricemia, metabolic alkalosis), pulmonary hypertension, and progressive renal failure in infancy (HUPRA syndrome). Analysis of the consanguineous pedigree suggested that the causative mutation is in the nuclear DNA. By using genome-wide SNP homozygosity analysis, we identified a homozygous identity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
128
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(137 citation statements)
references
References 23 publications
3
128
1
2
Order By: Relevance
“…Initially, this patient was suspected of having a YARS2 defect as we previously reported in an infant with lactic acidosis, sideroblastic anemia, and multisystem disease (cardiac hypertrophy) who succumbed in infancy (Riley et al 2013). Pulmonary hypertension, elevated serum lactate, anemia, premature birth, and death in infancy are also characteristics of patients with SARS2 mutations; patients also display progressive renal disease (Belostotsky et al 2011). For a growing number of aaRS2 family genes, genetic variants have resulted in two distinct phenotypes, usually a more moderate form and a severe, lethal infantile form.…”
Section: Discussionmentioning
confidence: 86%
“…Initially, this patient was suspected of having a YARS2 defect as we previously reported in an infant with lactic acidosis, sideroblastic anemia, and multisystem disease (cardiac hypertrophy) who succumbed in infancy (Riley et al 2013). Pulmonary hypertension, elevated serum lactate, anemia, premature birth, and death in infancy are also characteristics of patients with SARS2 mutations; patients also display progressive renal disease (Belostotsky et al 2011). For a growing number of aaRS2 family genes, genetic variants have resulted in two distinct phenotypes, usually a more moderate form and a severe, lethal infantile form.…”
Section: Discussionmentioning
confidence: 86%
“…Other nuclear-encoded mitochondrial translation defects have been linked to renal dysfunction. For example, mutations of SARS2, which affect the aminoacylation of tRNA serine, were recently reported in HUPRA syndrome (hyperuricaemia, pulmonary hypertension and renal failure in infancy with alkalosis) [22]. This is a fatal multisystem disorder in which affected infants have tubulointerstitial disease leading to salt wasting, hypomagnesaemia and end-stage renal failure by 1 year of age.…”
Section: Disorders Of Mitochondrial Translationmentioning
confidence: 99%
“…This is a fatal multisystem disorder in which affected infants have tubulointerstitial disease leading to salt wasting, hypomagnesaemia and end-stage renal failure by 1 year of age. Renal biopsy revealed various tubulo-interstitial changes, including dedifferentiated, atrophic tubules with thick basement membrane, some completely denuded tubules and hyperplastic arteriolitis in the interstitium [22]. Tubulopathy has also been reported in two other defects of mitochondrial translation: two sisters with MRPS22 mutations affecting the integrity of the mitochondrial small ribosome had tubulopathy with hypertrophic cardiomyopathy, hypotonia, lactic acidosis and hyperammonaemia, while a girl with mutations in TFSM encoding the translation elongation factor EFTs presented with intrauterine growth retardation, tubulopathy, hepatic insufficiency and hypotonia [23].…”
Section: Disorders Of Mitochondrial Translationmentioning
confidence: 99%
“…e genetic studies in [266][267][268] strongly suggest that such mitochondrial dysfunction can have a strong, causal role in PAH and one study used mitochondrial inhibitors which showed a complex causal role in PAH [269]. Four of these studies [264,266,268,269] all suggest mechanisms by which mitochondrial dysfunction may contribute to the symptoms and signs of PAH.…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Quite a number of studies have reported substantial mitochondrial dysfunction in PAH [264][265][266][267][268][269]. e genetic studies in [266][267][268] strongly suggest that such mitochondrial dysfunction can have a strong, causal role in PAH and one study used mitochondrial inhibitors which showed a complex causal role in PAH [269].…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%